2015
DOI: 10.1371/journal.pone.0131760
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased Expression of CoREST1 and CoREST2 Together with LSD1 and HDAC1/2 during Neuronal Differentiation

Abstract: CoREST (CoREST1, rcor1) transcriptional corepressor together with the histone demethylase LSD1 (KDM1A) and the histone deacetylases HDAC1/2 form LSD1-CoREST-HDAC (LCH) transcriptional complexes to regulate gene expression. CoREST1 belong to a family that also comprises CoREST2 (rcor2) and CoREST3 (rcor3). CoREST1 represses the expression of neuronal genes during neuronal differentiation. However, the role of paralogs CoREST2 and CoREST3 in this process is just starting to emerge. Here, we report the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…We then investigated the regulatory mechanism of KDM1A in SCAPs. KDM1A has been found to form protein complexes with other proteins during cell proliferation and differentiation . In the present study, we identified several candidate binding partners of KDM1A including PLOD2.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We then investigated the regulatory mechanism of KDM1A in SCAPs. KDM1A has been found to form protein complexes with other proteins during cell proliferation and differentiation . In the present study, we identified several candidate binding partners of KDM1A including PLOD2.…”
Section: Discussionmentioning
confidence: 69%
“…KDM1A has been found to form protein complexes with other proteins during cell proliferation and differentiation. [29][30][31] In the present study, we identified several candidate binding partners of KDM1A including PLOD2. Indeed, further study confirmed that KDM1A could bind with PLOD2 in SCAPs.…”
Section: Discussionmentioning
confidence: 90%
“…Two paralogues, CoREST2 and CoREST3, have been found in humans and also form a complex with REST (McGann et al, 2014;Jung et al, 2018). However, their transcriptional activity and expression profile in the human brain remains largely unknown (Barrios et al, 2014;Sáez et al, 2015). Research suggests that each CoREST protein may play a different role in neurodevelopment via targeting unique genes in neural and glial cell types during development (Abrajano et al, 2009a(Abrajano et al, ,b, 2010.…”
Section: Rest-mediated Gene Repressionmentioning
confidence: 99%
“…CoRest family members lack site‐specific DNA binding activity but associate with DNA through interactions with other proteins. CoRest1, together with lysine‐specific demethylase 1 (LSD1) and histone deacetylases (HDACs) 1/2, forms a powerful repressor known as the LSD1‐CoRest‐HDAC (LCH) complex . LSD1 binds to the second switching‐defective protein 3 (Swi3), adaptor 2 (Ada2), nuclear receptor co‐repressor (N‐CoR) and transcription factor (TF)IIIB (SANT) domain of CoRest and HDACs 1/2 bind to the Egl‐27 and MTA1 homology 2 (ELM2) and first SANT domain .…”
Section: Introductionmentioning
confidence: 99%
“…CoRest1, together with lysine-specific demethylase 1 (LSD1) and histone deacetylases (HDACs) 1/2, forms a powerful repressor known as the LSD1-CoRest-HDAC (LCH) complex. 15,16 LSD1 binds to the second switching-defective protein 3 (Swi3), adaptor 2 (Ada2), nuclear receptor co-repressor (N-CoR) and transcription factor (TF)IIIB (SANT) domain of CoRest and HDACs 1/2 bind to the Egl-27 and MTA1 homology 2 (ELM2) and first SANT domain. [17][18][19] LSD1 removes methyl groups from histone 3 at lysine 4 or 9 (H3K4/H3K9), 20 while HDACs remove acetyl groups from histone tails.…”
Section: Introductionmentioning
confidence: 99%